Identitas Visual pada Desain Feeds Instagram Brand “Zamzam Kalimantan” (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
Developments in the era of Industrial Revolution 4.0 are increasing rapidly along with the times, especially in the economic sector. The development of the economic sector in Indonesia means that MSMEs (Micro, Small, and Medium Enterprises) need strategies to brand themselves. Branding efforts can be carried out using social media platforms, namely Instagram. Instagram plays an important role as a promotional media that functions to persuade and communicate a product or service. This journal discusses the visual identity in the design of the Instagram feeds for the brand "Zamzam Kalimantan" as a portfolio of Kawakibi Digital Branding. This design uses qualitative methods based on interviews, observations, and literature studies. Through this process, designs for Instagram feeds were produced as Kawakibi's portfolio media.